Pengaruh Pemberian Insentif Pajak, Pengetahuan Perpajakan, Kualitas Pelayanan dan Penerapan E- System Terhadap Kepatuhan Wajib Pajak Orang Pribadi Selama Pandemi Covid-19 ( Studi Kasus Terhadap Wajib Pajak Orang Pribadi Yang Terdaftar di KPP Pratama Tange - Martin Yarangga (Komunitas Dosen Indonesia, 2022)
A virus that started in the Chinese city of Wuhan and continued to spread until it finally entered Indonesia. Where the virus caused many impacts, especially in the economic field. So many companies are reducing employees and even closing their business because there is no more income received. as well as to make tax payments became hampered so that finally the government implemented several policies in paying taxes. until finally the researchers were interested in seeing the level of compliance of individual taxpayers in carrying out their tax obligations. Where in this study aims to determine whether the provision of tax incentives, tax knowledge, service quality and the application of e-systems has an effect or not on individual taxpayer compliance during the covid-19 pandemic. The independent variables used are tax incentives, tax knowledge, service quality and e-system implementation. The dependent variable used is individual taxpayer compliance. The population in this study are individual taxpayers who are registered at KPP Pratama, West Tangerang until November 2021. The method used in obtaining samples in this study is the purposive sampling method, where the sample produced is 100 people. and the data collection technique used in this study is quantitative, where the researcher uses a method to distribute questionnaires and see the responses of taxpayers in carrying out their tax obligations. which is then after the data is collected, then the data is processed using the SPSS Version 24 program. Based on the data generated in this study, it shows that variables such as tax incentives, tax knowledge, and the application of e-systems affect individual taxpayer compliance during the COVID-19 pandemic. 19, but the service quality variable has no effect on taxpayer compliance. individuals during this COVID-19 pandemic to carry out their tax obligations